Semiotics Sign and Meaning in the Selected Logos of Coffee Shops in Pekanbaru - Asmira Farah Dinda; Lelly Zuyana Asril; Gunaldi Masbiran (Enlighted Journal, 2023)
Coffee shop is very popular in Indonesia. Coffee shop usually has logo which contain their own characteristic to identify the coffee shop. People usually start the conversation with each other, everyone can meet up with their friends in the coffee shop, people could talk, gathering, and relaxing. This study was to focused learnt about element of the sign and meaning through the coffee shops logos in Pekanbaru. The purpose of this research was to analyze what the elements of the sign and what the interpretant meaning of the sign in coffee shops logos. This research used qualitative method to describe the research about elements and interpretant sign in each coffee shop logo. This research using triadic semiotics theory which created by Charles Sanders Peirce to do analysis. Total data to analyze were 10 coffee shops in Pekanbaru. The result showed that The icon where to focus on the image or could be said the icon such as a half circle, manual coffee grinder handle, coffee bean grow some leaf, letter â€œDâ€ fill with house and grass, the bridge and plastic up with coffee bean, letter â€œAâ€ with coffee bean and roof house with letter â€œOâ€ fill with coffee bean. The index sign was to shown which had the name of their coffee shop. The symbols was to focus on the philosophical meaning of the logo color.